Penerapan Model Pembelajaran Inkuiri Sosial untuk Meningkatkan Hasil Belajar IPS Siswa Kelas V SDN 284 Labuaja Kecamatan Kahu Kabupaten Bone - Sitti Jauhar; Muliadi Muliadi; Rina Rina (Universtas Negeri Makassar, 2023)
This research is classroom action research (CAR). The approach used in this study is a descriptive qualitative approach, which aims to describe the application of the social inquiry learning model to improve social studies learning outcomes. The focus of this research is the application of the social inquiry learning model and the improvement of social studies learning outcomes. The setting of this research is SDN 284 Labuaja, Kahu sub-district, Bone district, in the 2021/2022 academic year. The research subjects were teachers and fifth grade students of SDN 284 Labuaja, with a total of 17 students consisting of 5 girls and 12 boys. Data collection techniques used are observation, test and documentation. The data analysis technique is a quantitative and qualitative approach. The results showed that there was an increase, both in teacher and student activities as well as learning outcomes in social studies subjects from cycle I with Enough qualification (C) increased to Good qualification (B) in cycle II. The conclusion of the study is that the application of the social inquiry learning model can improve social studies learning outcomes for fifth grade students at SDN 284 Labuaja, Kahu sub-district, Bone district.